Increasing Self Confidence Students Of SLB Negeri Singkawang with Hydroponic Vegetable Cultivation - Buyung, Buyung; Triani, Susan Neni; Marhayani, Dina Anika; Rosmaiyadi, Rosmaiyadi; Basith, Abd; Mayasari, Dian; Mursidi, Andi (STKIP Singkawang, 2023)
ABK (children with special needs) who are introverted, shy towards themselves, their self-confidence is still low and there are no ongoing activities to develop soft skills (skills). The purpose of this service activity can make ABK open themselves to a new environment, can increase the confidence of ABK, and form a sustainable hydroponic vegetable cultivation program to improve the skills of ABK through planting vegetables with hydroponic techniques. Method This program is realized through the SPP method (socialization, training and mentoring), namely through direct practice in the field. The method of implementing this program is described in the stages of implementing field activities which include preparation of the program implementing team, outreach to the program, preparation of equipment and tools, formation of activity groups, introduction to activities, creation of hydroponic media, practice of cultivating vegetables with hydroponic techniques, monitoring and evaluation of implementation. activity program. Results of activities the percentage of student responses from self-confidence questionnaires through hydroponic cultivation shows that most ABK (Children with Special Needs) in Singkawang State SLB have self-confidence with a percentage of 87.80% (Very good). From the observation table above, it was obtained that the average percentage of ABK soft skills in hydroponic farming was 93% in the very good category. While the average percentage of ABK's soft skills that are still unable to practice is 7% with a very low category.